Critérios para a seleção de áreas prioritárias para a criação de unidades de conservação em áreas urbanas - Ribeiro, Juliana Baladelli (2012)
The selection of areas for the establishment of new protected areas (PAs) has not necessarily been based on technical criteria. In most cases, areas are chosen due to favorable conditions, such as appropriate landscape, policy issues or the existence of environmental constraints in the area, as the inability to implement diferent activities on site. These facts enable the selection of areas that are probably less favorable in terms of nature conservation. In urban areas, where land generally has a higher cost and the anthropogenic pressure for the use of the area is more intense, it becomes even more difficult to choose areas for the creation of protected areas. The existence of technical criteria for the creation of protected areas in urban location would assist managers in selecting areas with better conditions of biodiversity conservation. Given this fact, the aim of this work is to establish standards for the selection of priority areas for the creation of new protected areas in urban areas and assess the environmental services related to them, justifying public investment in PAs. The methodology selected for the survey was based on scientific articles, technical documents and legal regulations. Different criteria used around the globe were adopted in the selection of new areas for the creation of the PAs. Based on it, it was possible to prioritize the areas by their effectiveness for the conservation of the nature, by using the criteria previously adopted. For assessment criteria and environmental services associated with the PAs, forms were applied to experts in Nature Conservation in Brazil. To analyze the results of the forms were made quantitative and qualitative analyzes. Based on the criteria evaluated by experts, it was created a tool to aid decision making in the selection and prioritization of areas for the creation of protected areas, in order to ensure the effectiveness of biodiversity conservation. This tool allows the selection of areas for the creation of PAs more objectively and based on scientific criteria.